First flights - Stewart, Oliver, Major, 1895-1976 (Routledge and Kegan Paul, 1957)
First Flights Aviation's early heroes. The touchstone of practical achievement, sorting fact from fiction -- The first airmen of all -- Sir George Cayley's genius -- Enter the pilot. From glider to powered aeroplane -- Control and stability -- Ader and Santos-Dumont -- Despite the doubters, the Wright brothers fly alone -- Proof. The first Channel flight and its implications -- The first aerobatic flights. Pégoud's name remains in aviation history as that of the first aerobatic pilot -- War achievements. The first air combats and the origination of aerial tactics -- The greatest test. The Atlantic Ocean as the supreme challenge of the period following the first world war -- Speed is the aim. Racing and record breaking as incentives to progress -- Empire air lines. The beginnings of commercial aviation -- The role of the flying-boat -- Around the world. Post and Gatty perform a feat of historic importance -- Soloists. Lindbergh and the other great solo flyers -- Jet aircraft. Turbojets, turboprops, rockets and ram jets -- Early British and German work -- Jet harvest. The first record-breaking flight with jet-propelled aircraft -- New speeds and altitudes -- The comet story. The introduction of the first jet-propelled air-liner was the greatest technical advance yet seen in the whole field of transport aviation -- Helicopters. The progress of moving-wing flight has run concurrently with that of fixed-wing flight -- It owes much to the genius of one man -- Powered lift. Aeroplane use power indirectly to secure lift, but designs have been prepared of machines which will use power directly for obtaining lift -- Among them is the flying bedstead -- Future flights. Space flight as the ultimate objective -- The powered-lift aircraft for passenger travel Includes index; Includes references to Newfoundland